Agammaglobulinaemia in a girl with a mosaic of ring 18 chromosome - Litzman, J; Brysová, V; Gaillyová, R; Thon, V; Pijácková, A; Michalová, K; Zemanová, Z; Lokaj, J (Journal of paediatrics and child health, 1998)
A patient with a mosaic karyotype 45,XX,-18/46,XX,dic r(18)/46,XX,r(18) with multiple phenotypic abnormalities and immunodeficiency was presented at the age of 14 years. Immunological investigation revealed markedly decreased IgG, IgA and in two of three evaluations also IgM levels. Although selective IgA deficiency is frequent in patients with a ring chromosome 18, this is the third patient described with decreased levels of other immunoglobulin isotypes. The association of chromosome 18 partial deletions and immunoglobulin abnormalities suggests the presence of an as yet unrecognised gene with a pivotal role for immunoglobulin production on chromosome 18.
Keywords: mozaicismus; Adolescent; agamaglobulinemie; Chromosomes, Human, Pair 18; lidé; Female; lidské chromozomy, pár 18; Chromosome Disorders; Chromosome Aberrations; Ring Chromosomes; chromozomální aberace; mladiství; kruhové chromozomy; Mosaicism; Agammaglobulinemia; ženské pohlaví; chromozomální poruchy; Humans